Impact of Crude Oil Price Volatility on Procurement and Inventory Strategies in the Middle East - Mohammad, Suleiman Ibrahim Shelash; Al-Daoud, Khaleel Ibrahim; Al Oraini, Badrea Saleh; Alqahtani, Menahi Mosallam; Vasudevan, Asokan; Ali, Imad (International Journal of Energy Economics and Policy, 2025)
Crude oil price volatility is a critical factor influencing procurement costs and inventory management in oil-dependent industries. This study examines the impact of crude oil price fluctuations on procurement expenses and inventory turnover, providing empirical insights into how businesses respond to oil market uncertainties. Given the direct link between oil price changes and supply chain costs, understanding these relationships is essential for developing risk mitigation strategies and enhancing supply chain resilience. The study employs time series analysis (ARIMA), econometric modelling (multivariate regression), and sensitivity analysis to quantify the effects of crude oil price volatility on procurement and inventory decisions. Data from multiple firms across industries were analysed to assess how fluctuations in oil prices influence procurement expenses, inventory turnover, and firm-level procurement strategies. Results indicate that higher crude oil price volatility leads to a significant increase in procurement costs, with an estimated impact of 3.96 million per unit increase in volatility. Additionally, inventory turnover declines as oil price volatility rises, as firms tend to hold onto stock longer to hedge against price uncertainty. Larger firms experience higher procurement costs but benefit from economies of scale, while smaller firms rely on agility and flexible sourcing strategies to manage cost fluctuations. The findings emphasize the need for predictive analytics, supplier diversification, and adaptive inventory management to mitigate procurement risks. Businesses must adopt data-driven procurement strategies and AI-driven forecasting models to navigate crude oil price uncertainties effectively. Future research should explore industry-specific procurement trends and the role of sustainability in reducing oil price dependencies.